2017
DOI: 10.18632/oncotarget.22173
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic-induced activation of human aryl hydrocarbon receptor target genes inDrosophilais mediated by the epigenetic chromatin modifiers

Abstract: Aryl hydrocarbon receptor (AHR) is the key transcription factor that controls animal development and various adaptive processes. The AHR’s target genes are involved in biodegradation of endogenous and exogenous toxins, regulation of immune response, organogenesis, and neurogenesis. Ligand binding is important for the activation of the AHR signaling pathway. Invertebrate AHR homologs are activated by endogenous ligands whereas vertebrate AHR can be activated by both endogenous and exogenous ligands (xenobiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…We have previously demonstrated that Drosophila may serve as a valid model organism to investigate the complex effects of xenobiotics on human AHR functioning in vivo [32]. In order to investigate the effects of xenobiotics on male fecundity, we used Drosophila males carrying inducible human AhR (the UAS-AhR construct is described in Reference [32]) and Tj-GAL4 drivers. In Drosophila testes, the Tj-GAL4 driver activates UAS -constructs in cells which are in connection with generative cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that Drosophila may serve as a valid model organism to investigate the complex effects of xenobiotics on human AHR functioning in vivo [32]. In order to investigate the effects of xenobiotics on male fecundity, we used Drosophila males carrying inducible human AhR (the UAS-AhR construct is described in Reference [32]) and Tj-GAL4 drivers. In Drosophila testes, the Tj-GAL4 driver activates UAS -constructs in cells which are in connection with generative cells.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the ability of xenobiotics to influence the expression of human AHR target genes in Drosophila testes, we first identified potential human AHR target genes in Drosophila (described in Reference [32]). We selected several putative Drosophila homologs of human AHR targets genes containing XRE -elements in their regulatory regions: Mannosyl (α-1,3-)-glycoprotein β-1,2-N-acetylglucosaminyltransferase 1 ( Mgat1 ), which participates in the determination of adult lifespan relating to mushroom body development; Glutathione S transferase T4 ( GstT4 ), which is involved in oxidation-reduction processes and catalyzes reactions of biotransformation; Cytochrome P450 6g1 ( Cyp6g1 ), which is involved in the oxidation-reduction process, response to DDT, and the insecticide catabolic process; N-acetylneuraminic acid synthase ( Nans ), which participates in the carbohydrate biosynthetic process; Relish ( Rel ), which encodes the NF-κB subunit; p53 , which is a transcriptional factor required for adaptive responses to genotoxic stresses, including cell death, compensatory proliferation and DNA repair; Myc, a transcription factor related to proto-oncogenes, which contributes to cell growth, cell competition, and regenerative proliferation; dаcapo ( dap ), which encodes the Cyclin-dependent kinase inhibitor; the Retinoblastoma-family protein ( Rbf ), which provides negative regulation of the G1/S transition of mitotic cell cycles; Jun-related antigen ( Jra ), which is involved in positive regulation of the metabolic process, humoral immune response, aging, and RNA polymerase II transcription factor activity; and Dcdc42 ( Cdc42 ), which is a key regulator of the actin cytoskeleton, playing a central role in actin cytoskeleton organization, morphogenesis, hemocyte migration, cell polarity, and wound repair.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations